Tratamiento Multidisciplinario del Cáncer de Mama en Estadio Clínico III: Quimioterapia, Cirugía y Radioterapia - Chávez de Paz, Carlos (1998)
A prospective study, in which women with clinically stage III breast cancer underwent multidisciplinary therapy by using primary (neoadyuvant) chemotherapy, followed randomly by loco-regionally therapy, either with surgery or radiotherapy; and postoperative systemic chemotherapy (coadyuvant), in both groups of treatment, was conduced at the Peruvian Institute of Neoplasic Diseases. This is a randomized, prospective, descriptive, interventionist and analitical clinical study. Clinical response to primary chemotherapy was positive in 80,23% of cases, complete resolution was observed in 18,60% of cases, partial resolution in 61,63% of cases and there was absolutely no response in 19,77% of cases. No residual neoplasm, patologically proven,was observed in 8,33% of surgical cases. We demonstrated that high-dose primary chemotherapy, using only 2 drugs (cyclophosfamide and 5-fluorouracil), used here because of its lower price, brougth similar results compared to anthracycline-containing regimens. Recurrence rates were similar and showed no significative differences in both groups of treatment. Both, the disease-free survival (DFS) and overall survival (OS), were similar in both groups of treatment. We also demonstrated that in patients who underwent surgery, the lower the number of homoaxillary lymph node metastases, the higher the overall survival (OS) time. Patients with clinically stage III (A or B) breast cancer, showed similar clinical responses to neoadyuvant chemotherapy, they also showed similar recurrence rates, DFS and OS, when treated with radical mastectomy or radiotherapy.